Dynamic Response of a Long-Span Concrete-Filled Steel Tube Tied Arch Bridge and the Riding Comfort of Monorail Trains - Hongye Gou (Department of Bridge Engineering, School of Civil Engineering, Southwest Jiaotong University, Chengdu 610031, China) (MDPI AG, 2018)
In this study, a dynamic response analysis procedure is proposed and applied to investigate the dynamic responses of a straddle-type concrete-filled steel tube tied arch bridge under train and truck loadings. A numerical model of the coupled monorail train–bridge system is established to investigate the dynamic behaviors of the bridge under moving trains. A refined three-dimensional finite element model is built for the bridge and a 15 degrees-of-freedom vehicle model is presented for the train. The numerical model is validated using in-situ test results and then used to analyze the dynamic displacement and acceleration of the bridge and the trains on the bridge. Based on the simulation results, the impact factor of the bridge is investigated and the riding comfort of the trains is evaluated. The investigation results show that the impact factor of vehicle loads reaches the maximum value when the resonance of the bridge is induced by the moving vehicles. The effect of train braking predominates the longitudinal vibration of the bridge but is negligible in the transverse and vertical directions. The vehicle speed is the dominating factor for the riding comfort of the train.